Sobre o teor de vitamina c em mirtáceas - Brune, Walter; M Batista, Cid; O Silva, Daison; Maurício Fortes , José; V R Pinheiro, Rubens (Revista Ceres, 2025)
The contents of vitamin C of fruits of several Myrtaceae were measured by a new technique. This allows far analysis of samples of difficult filtration aswellas those with high contents of anthocyanins. The results show various species to have notably high yields of this vitamin, Eugenia dombeyi, Skeels; E. uvalha, Camb. ; E. uniflora, L.; E. tomentosa, Camb.; Myrciaria cauliflora, Berg. e E, Luschnathiana Klatzch ex Berg. Storage of the unprocessed fruits in freezers destroys the vitamin in a short time. Thus, within two weeks the loss of vitamin was complete. Oxalic acid, on the other hand, when admixed with the desintegrated fruits preserves the amounts of vitamin for a week or so. No significant reduction was noted during this period.